Combined Effect of Sarcopenia and Systemic Inflammation on Survival in Patients with Advanced Stage Cancer Treated with Immunotherapy. (5th December 2019) - Bilen, Mehmet Asim; Martini, Dylan J.; Liu, Yuan; Shabto, Julie M.; Brown, Jacqueline T.; Williams, Milton; Khan, Amir I.; Speak, Alexandra; Lewis, Colleen; Collins, Hannah; Kissick, Haydn T.; Carthon, Bradley C.; et al.
Abstract: Background: Sarcopenia and inflammation have been associated with poor survival in patients with cancer. We explored the combined effects of these variables on survival in patients with cancer treated with immunotherapy. Methods: We performed a retrospective review of 90 patients enrolled on immunotherapy‐based phase I clinical trials at Emory University from 2009 to 2017. Baseline neutrophil‐to‐lymphocyte ratio, monocyte‐to‐lymphocyte ratio, and platelet‐to‐lymphocyte ratio (PLR) were used as surrogates of inflammation. The skeletal muscle index (SMI) was derived from the skeletal muscle density calculated from baseline abdominal computed tomography images. Optimal cutoffs for continuous inflammation biomarkers and SMI were determined by bias‐adjusted log‐rank test. A four‐level risk stratification was used to create low‐risk (PLR <242 and nonsarcopenic), intermediate‐risk (PLR <242 and sarcopenic), high‐risk (PLR ≥242 and nonsarcopenic), and very‐high‐risk (PLR ≥242 and sarcopenic) groups with subsequent association with survival. Results: Most patients (59%) were male, and the most common cancers were melanoma (33%) and gastrointestinal (22%). Very high‐risk, high‐risk, and intermediate‐risk patients had significantly shorter overall survival (hazard ratio [HR], 8.46; 95% confidence interval [CI], 2.65–27.01; p < .001; HR, 5.32; CI, 1.96–14.43; p = .001; and HR, 4.01; CI, 1.66–9.68; p = .002, respectively) and progression‐free survival (HR, 12.29; CI, 5.15–29.32; p < .001; HR, 3.51; CI, 1.37–9.02; p = .009; and HR, 2.14; CI, 1.12–4.10; p = .022, respectively) compared with low‐risk patients. Conclusion: Baseline sarcopenia and elevated inflammatory biomarkers may have a combined effect on decreasing survival in immunotherapy‐treated patients in phase I trials. These data may be immediately applicable for medical oncologists for the risk stratification of patients beginning immunotherapeutic agents. Abstract : The interaction between chronic inflammation and body composition is particularly important in the era of immunotherapy, considering that immune checkpoint inhibitors rely on the host immune system for their efficacy. This article reports on the combined effects of inflammation and sarcopenia on clinical outcomes in patients with solid tumors treated with immunotherapy‐based regimens.